2011
DOI: 10.1002/pd.2661
|View full text |Cite
|
Sign up to set email alerts
|

Fetal micrognathia: objective assessment and associated anomalies on prenatal sonogram

Abstract: The diagnosis of micrognathia has a crucial impact on both prenatal and postnatal outcomes of affected individuals due to its association with additional abnormalities. A detailed sonographic survey using objective criteria for defining micrognathia is mandatory. Once the diagnosis is confirmed, an intensive interdisciplinary counseling of the parents is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 29 publications
7
78
0
7
Order By: Relevance
“…Daha objektif bir değerlendirme için literatürde çeşitli indeks ve açı ölçümleri tanımlanmıştır. Çene indeksi ("jaw index"), inferior fasiyal açı ve frontal nazomental açı ölçümleri bunlara örnektir [32,33].…”
Section: Yüz Profi̇li̇nde Saptanabi̇lecek Di̇ğer Anormalli̇klerunclassified
“…Daha objektif bir değerlendirme için literatürde çeşitli indeks ve açı ölçümleri tanımlanmıştır. Çene indeksi ("jaw index"), inferior fasiyal açı ve frontal nazomental açı ölçümleri bunlara örnektir [32,33].…”
Section: Yüz Profi̇li̇nde Saptanabi̇lecek Di̇ğer Anormalli̇klerunclassified
“…Luedders et al 44 suggested that normal development of the mandible depends on mandibular movement during intrauterine development. According to Terzis and Anesti, 45 this condition has been observed in newborns with reports ranging from 1.4 up to 64 per 1000 birth.…”
Section: Use Of Ultrasound Images Can We Use Fetal Facial Movements Fmentioning
confidence: 99%
“…According to Terzis and Anesti, 45 this condition has been observed in newborns with reports ranging from 1.4 up to 64 per 1000 birth. Given the importance of this condition, Luedders 44 argued for 3D ultrasound visualization, which facilitates the identification of facial anomalies in planes that cannot be obtained by conventional 2D imaging. This multiplanar navigation, which is only possible with 3D technology, provides valuable information by enabling the visualization of fetal facial structures from multiple perspectives.…”
Section: Use Of Ultrasound Images Can We Use Fetal Facial Movements Fmentioning
confidence: 99%
“…This metric demonstrated a sensitivity of 100.0% and a specificity of 98.1%. While accurate, it has been noted that the jaw index is both more difficult and time consuming to measure accurately than more recently developed measures [21]. …”
Section: Micrognathiamentioning
confidence: 99%
“…Luedders et al [21] retrospectively analyzed 58 cases of postnatally diagnosed micrognathia using IFA and FNM angles. Fifty-four of the 58 cases (93%) were validated using the cutoffs of 142° for the FNM angle and 50° for the IFA.…”
Section: Micrognathiamentioning
confidence: 99%